Atrial Fibrillation and the Role of LAA in Pathophysiology and Clinical Outcomes? - Saygi, Serkan (J Atr Fibrillation, 2012)
Left atrial appendage (LAA) is a source of thromboembolism especially in patients with non valvular atrial fibrillation (AF). It is reasonable to accept LAA as a distinct part of left atrium (LA) with unique anatomical and physiological properties. Advances in imaging modalities increased the knowledge about anatomical and physiological characteristics of LAA. It is important to prevent the AF patients from systemic thromboembolic events, and new pharmacological and non pharmacological management approaches demonstrate encouraging results. Also pulmonary vein isolation which has been accepted as a curative and useful treatment option for the treatment of drug resistant AF has been helpful in understanding the electrophysiological properties of LAA. Accumulating data revealed that LAA continues to be the one of the most important structure of heart during AF because of its distinctive anatomical, mechanical, and electrophysiological properties.